Keragaman Genus Anadara Berdasarkan Karakter Morfologis dan Habitat di Perairan Pantai, Kota Tarakan, Kalimantan Utara - Z. Zainuddin; Nyoman Puniawati Soesilo; T. Trijoko (Journal of Tropical Biodiversity and Biotechnology, 2018)
Bivalves are actively captured to be used as foodstuffs and raw materials souvenirs. Bivalves have economic value that continues to be exploited. But there is no record of its biodiversity in the coastal waters Tarakan City. This research purposes were to study the members of the Genus Anadara species diversity, study of morphological characters and its habitats in the waters of Tarakan. The method used in sampling was transect methods. Four stations have been set i.e. Binalatung, Selayung, Juata and airport. The obtained bivalves were identified based on its morphological characters. Physicochemical of the water, substrate, and the substrate texture in each station were measured. The morphological data was analyzed using descriptive analysis, while the relationships between shells’ morphometric was analyzed using linear regression analysis.The result of this research showed that there are two  species, Anadara granosa and Anadara nodifera. Morphological character showed that there are radial ribs both of  species. Habitat character is dominated by sand and mud. Morphometric relationships shells can be used to distinguish each species.